DISPARITAS PUTUSAN MALPRAKTEK KEDOKTERAN STUDI PUTUSAN MAHKAMAH AGUNG NO. 365K/PID/2012 - AHMAD YASIR LUBIS (LP2MTBM MAKARIOZ, 2020)
Data of the Indonesian Medical Discipline Honorary Assembly (MKDKI) shows that cases of malpractice by obstetricians arequite high. For example, the malpractice case that reached trial to the Supreme Court was a team of doctors consisting of dr.Ayu, dr. Hendi Siagian, and dr. Henry Simanjuntak at Dr. Kandau Manado Hospital against the victim, Julia FransiskaMakatey. Another case, the malpractice case resulted in the supreme court judge's ruling, namely Supreme Court Ruling No.365K/Pid/2012. The form of criminal acts committed by doctors in carrying out their profession is divided into threecategories, namely (1) criminal malpractice of willful nature; (2) Criminal Malpractice of carelessness; and (3) CriminalMalpractice that is opassive. The basis of the Supreme Court Judge's consideration in dismissing case No. 365K/Pid/2012 isthat medical actions taken against patients, whether in terms of diagnosis, therapeutic and disease management performed,have violated the law, propriety, decency and professional principles. the basis of consideration is that the Defendantperformed medical actions in accordance with the prevailing orational standards of procedure, competence, and ethics.